Analysis of Motivation, Training, Competence and Employee Performance at the Mojokerto Regency Regional Development Planning Agency - Dody Prasetyo; Ernani Hadiyati; Sugeng Mulyono (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Purpose - The purpose of this study was to determine and analyze the effect ofmotivation and training on employee performance by mediating the competency ofthe employees of the Mojokerto Regency Regional Development Planning Agency.Design/Methodology/Approach – This type of research uses a survey approach. Thefamous survey research is The Gallup Poll which is intended to find out people'sopinions. Based on the level of explanation, this research can also be grouped intoassociative research. Associative research, namely research that links or morevariables, for example looking at the influence of coach factors and work motivationon employee performance. As for this study, the researchers decided to take theresearch population with the target or object, namely employees at the RegionalDevelopment Planning Agency Office of Mojokerto Regency, a total of 50 people.Data analysis used Partial Least Square (PLS) analysis.Findings - The results of this study explain that employee competence is not amediating variable in this study. The influence of motivation and training is directlyproven to be able to improve employee performance and even employee competencecan directly improve employee performance. It has not been proven that employeecompetence in this research model as mediation has not been proven, this isexplained in the discussion